Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(B=3+3^2+3^3+.....+3^{2006}\)
\(\Rightarrow3B=3^2+3^3+....+3^{2007}\)
\(\Rightarrow2B=3^{2007}-3\)
\(\Rightarrow B=\frac{3^{2007}-3}{2}\)
\(2B+3=3^x\)
\(\Rightarrow2.\frac{3^{2007}-3}{2}+3=3^x\)
\(\Rightarrow3^{2007}-3+3=3^x\Rightarrow3^{2007}=3^x\Rightarrow x=2007\)
1. Tim x
a. ( \(\frac{8}{27}\))x = ( \(\frac{2}{3}\))72
b. \(\frac{1}{3}\) . 3x = 7 . 32 . 92 - 2 . 3x
a. \(\left(\frac{8}{27}\right)^x=\left(\frac{2}{3}\right)^{72}\)
\(\left(\frac{2}{3}\right)^{3x}=\left(\frac{2}{3}\right)^{72}\)
\(\Rightarrow3x=72\Rightarrow x=24\)
Vậy x = 24
a, \(\frac{x-1}{9}=\frac{8}{3}\Leftrightarrow\frac{x-1}{9}=\frac{24}{9}\Leftrightarrow x-1=24\Leftrightarrow x=25\)
b, \(\frac{x+2}{3}=\frac{2x-1}{5}\Leftrightarrow\frac{5x+10}{15}=\frac{6x-3}{15}\Leftrightarrow5x+10=6x-3\)
\(\Leftrightarrow5x+10-6x+3=0\Leftrightarrow-x+13=0\Leftrightarrow x=13\)
a) \(\frac{x-1}{9}=\frac{8}{3}\)
\(\Leftrightarrow3\left(x-1\right)=8.9\)
\(\Leftrightarrow3x-3=72\)
\(\Leftrightarrow3x=75\)
\(\Leftrightarrow x=25\)
b) \(\frac{x+2}{3}=\frac{2x-1}{5}\)
\(\Leftrightarrow5\left(x+2\right)=3\left(2x-1\right)\)
\(\Leftrightarrow5x+10=6x-3\)
\(\Leftrightarrow5x-6x=-3-10\)
\(\Leftrightarrow-x=-13\)
\(\Leftrightarrow x=13\)
\(-5.\left(x+\frac{1}{5}\right)-\frac{1}{2}.\left(x-\frac{2}{3}\right)=\frac{3}{2}x-\frac{5}{6}\)
\(\Rightarrow-5x-1-\frac{1}{2}x+\frac{1}{3}=\frac{3}{2}x-\frac{5}{6}\)
\(\Rightarrow-5x-\frac{1}{2}x-\frac{3}{2}x=\frac{-5}{6}-\frac{1}{3}+1\)
\(\Rightarrow-7x=\frac{-1}{6}\)
\(\Rightarrow x=\frac{1}{42}\)
Vậy ...
\(\)
\(3.\left(3x-\frac{1}{2}\right)^3+\frac{1}{9}=0\)
\(\Rightarrow3.\left(3x-\frac{1}{2}\right)^3=\frac{-1}{9}\)
\(\Rightarrow\left(3x-\frac{1}{2}\right)^3=\frac{-1}{27}\)
\(\Rightarrow\left(3x-\frac{1}{2}\right)^3=\left(\frac{-1}{3}\right)^3\)
\(\Rightarrow3x-\frac{1}{2}=\frac{-1}{3}\)
\(\Rightarrow3x=\frac{1}{6}\)
\(\Rightarrow x=\frac{1}{18}\)
Vậy...
\(=-2.\frac{2}{3}.\frac{1}{3}:\left(\frac{-1}{6}+0,5\right)-\left(-2009^0\right)-\left(-2\right)^2\)
\(=\frac{4}{3}.\frac{1}{3}:\left(\frac{-1}{6}+\frac{1}{2}\right)-1.4\)
\(=\frac{4}{3}.\frac{1}{3}+4\)
\(=4+4\)
\(=8\)
Tự ghi đề nhé!
a. \(\frac{-3}{4}:x=\frac{-11}{36}+\frac{1}{2}\)
= 7/36
x = 7/36 : -3/4 = -7/27
Tim x biet
a) x - \(\frac{5}{7}\)=\(\frac{1}{9}\)
b)\(\frac{-3}{7}\)- x = \(\frac{4}{5}+\frac{-2}{3}\)
\(x-\frac{5}{7}=\frac{1}{9}\)
\(x=\frac{52}{63}\)
\(\frac{-3}{7}-x=\frac{4}{5}+\frac{-2}{3}\)
\(\frac{-3}{7}-x=\frac{2}{15}\)
\(x=\frac{-59}{105}\)
\(2.THPT\)
\(A=\frac{9}{1.2}+\frac{9}{2.3}+\frac{9}{3.4}+...+\frac{9}{98.99}+\frac{9}{99.100}\)
\(A=9\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{99.100}\right)\)
\(A=9\left(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{99}-\frac{1}{100}\right)\)
\(A=9\left(1-\frac{1}{100}\right)\)
\(A=9.\frac{99}{100}\)
\(A=\frac{891}{100}\)
\(B=\frac{2}{5.7}+\frac{2}{7.9}+\frac{2}{9.11}+...+\frac{2}{93.95}\)
\(B=\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+\frac{1}{9}-\frac{1}{11}+...+\frac{1}{93}-\frac{1}{95}\)
\(B=\frac{1}{5}-\frac{1}{95}\)
\(B=\frac{18}{95}\)
\(D=\frac{5}{2.7}+\frac{4}{7.11}+\frac{3}{11.14}+\frac{1}{14.15}+\frac{13}{15.28}\)
\(D=\frac{1}{2}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{14}+\frac{1}{14}-\frac{1}{15}+\frac{1}{15}-\frac{1}{28}\)
\(D=\frac{1}{2}-\frac{1}{28}\)
\(D=\frac{13}{28}\)
\(\left(x+\frac{3}{2}\right)^2=\frac{9}{49}\)
\(\Rightarrow\left(x+\frac{3}{2}\right)^2=\left(\frac{3}{7}\right)^2\)
\(\Rightarrow x+\frac{3}{2}=\frac{3}{7}\)
\(\Rightarrow x=\frac{3}{7}-\frac{3}{2}\)
\(\Rightarrow x=\frac{-15}{14}\)
Vậy \(x=\frac{-15}{14}\)
_Chúc bạn học tốt_
(x+3/2)2=9/49
x+3/2=3/7
X=3/7-3/2
x=6-21/14
x=-15/14